Microstructure and Mechanical Properties of Heat Treatment Low-alloy Wear-resistant Steel NM450 - Wu Zhennan, Yao Kaiyang, Tao Yun, Zhou Weichen, WanXin , Song Xinli (Teshugang)
The effects of quenching and tempering at different temperatures on the microstructure， strength and wear resistance of NM450 high strength low-alloy wear-resistant steel were studied. The results showed that the lath martensite with a small amount of ferrite structure was obtained for the high-strength low-alloy wear-resistant steel quenched at 840 ℃ and tempered at 200 ℃. The lath martensite was obtained and the martensite matrix contains high-density dislocation， and the residual austenite was distributed between the martensite lath for the steel quenched at 880 ℃-900 ℃ and tempered at 200 ℃.With the increase of quenching temperature， the yield strength of wear-resistan steel NM450（/%：0.20C，0.50Si，2.0Mn，0.20Cr，0.03Als，≤0.015P，≤0.005S）was between 1142 MPa and 1 173 MPa， the tensile strength was between 1 553 MPa and 1 599 MPa， the elongation was between 10.0% and 12.0%. The strengthening mechanism of the test steel was mainly dislocation strengthening and fine grain strengthening and solid solution strengthening. There were a lot of furrows and grinding chips of the steels for abrasive wear， and the wear mechanism was mainly plastic deformation. The strength and wear-resistance proformance was the best for the steel quenched at 880 ℃ and the tempered at 200 ℃.